BEBERAPA PARAMETER YANG BERPENGARUH PADA STUDI INTERAKSI ION LOGAM – ASAM HUMUS - Budi Setiawan (Jurnal Ecolab, 2009)
Dissolved humic acids in groundwater are considered to interact with metal ions such as heavy metals or radionuclides.In their interaction with existing metal ions in groundwater are predicted to form metal ion-humic complexbinding such as humic acid-metal ion colloids. These complex colloid will migrate through groundwater flowwith similar velocity to disperse the contaminant into environment. For that reason the study of complex formationbetween humic acid and metal ions becomes important to be studied. Important parameters affecting metalion-humic acid interaction study are pH, ionic strength and metal ion concentrations. Objective of the study is tounderstand important parameters to affect the humic acid-metal ions interaction to form complex formation. Apparentcomplex formation of humic acid-metal ion is defined as ba = [ML]/[M][R], where [M] and [ML] are freeand bound of metal ion concentrations, and [R] = CRα (CR is total concentration of protonation exchange site anda degree of dissosiation of humic acid). Obtained results shown that logba of humic acid increased with loga anddecreased with ionic strength, and metal ion concentrations